Edukasi dan Pelatihan pada Ibu Nifas untuk Melakukan Pilates Exercise di Puskesmas Pulo Bandring Kisaran - Putri, Maidina; Khairani, Khairani (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The postpartum period can be interpreted as a period of recovery after childbirth until the reproductive organs function again as before pregnancy, Pilates gymnastics is a training program that focuses on flexibility and flexibility of all parts of the body. The purpose of this PkM activity is to provide education and training for postpartum mothers to do Pilates Exercise at the Pulo Bandring Kisaran Health Center. The implementation method for this PkM activity is in the form of education, counseling and training on pilates gymnastics movements. The implementation of this PkM is divided into 3 parts, namely, preparation of activities, implementation of activities and evaluation. The results of this PkM activity on the level of knowledge or understanding of the participants can be seen from the results after being given pilates knowledge in the post-test results. After being given counseling and re-measured, the post-test results showed that most of them understood about pilates knowledge, namely in the good category as many as 14 respondents (82.4%). It was concluded that there was an increase in postpartum mothers' knowledge about pilates after being given health counseling and demonstrations which can be seen from the higher post-test scores after being given treatment.